Spinal cord involvement in Lewy body-related α-synucleinopathies - Nardone, Raffaele (J Spinal Cord Med, 2019)
Context: Lewy body (LB)-related α-synucleinopathy (LBAS) is the neuropathological hallmark of several neurodegenerative diseases such as Parkinson disease (PD), but it is also found in neurologically asymptomatic subjects. An abnormal accumulation of α-synuclein has been reported also in the spinal cord, but extent and significance of the spinal cord involvement are still poorly defined. Objective: We aimed to review the studies addressing the spinal cord involvement of LBAS in healthy subjects and in patients with PD or other neurodegenerative diseases. Methods: A MEDLINE search was performed using following terms: “spinal cord”, “ α-synucleinopathy”, “α-synuclein”, “Lewy body”, “Parkinson’s disease”, “multiple system atrophy”, “neurodegenerative disorder”. Results: LBAS in the spinal cord is associated with that of the medullary reticular formation and locus ceruleus in the brainstem but not with that in the olfactory bulb and amygdala. The intermediolateral columns of the thoracic and sacral cord are the most frequently and severely affected region of the spinal cord. LBAS occurs in centrally projecting spinal cord neurons integrating pain, in particular from lower body periphery. It also involves the sacral parasympathetic nucleus innervating the smooth muscles of the bladder and distal colon and the Onuf’s nucleus innervating the striated sphincters. The spinal cord lesions may thus play a crucial role in the genesis of frequent non-motor symptoms such as pain, urinary symptoms, bowel dysfunction, autonomic failure including orthostatic hypotension and sexual disturbances. Moreover, these may also contribute to the motor symptoms, since α-synuclein inclusions have been observed in the pyramidal tracts of patients with PD and multiple system atrophy. Conclusion: Recognition of this peculiar spinal cord pathology may help in the management of the related symptoms in subjects affected by α-synucleinopathies.